Making Banking Platforms AI-Ready: The Data Engineering Foundation - Joshi, Rahul (International Journal of Computing and Engineering, 2025)
The financial services sector is experiencing a pivotal transformation as artificial intelligence is set to change underwriting, fraud identification, and the improvement of customer experience. Nevertheless, effectively integrating AI into banking demands much more than just complex algorithms or cutting-edge machine learning techniques. Effective AI deployment depends on a strong data engineering framework capable of meeting the intricate demands of regulated financial settings. Banking platforms ready for AI must go beyond basic machine learning integration to create holistic ecosystems centered on fundamental principles of reproducibility, explainability, security, and adherence to regulations. These systems necessitate advanced multi-zone designs that establish distinct separations between data processing phases while ensuring smooth integration throughout large-scale organizational functions. Feature engineering functions must address intricate temporal connections present in financial data via advanced versioning systems that monitor feature development and ensure backward compatibility. Thorough governance frameworks go beyond conventional data management to include model lineage, feature provenance, and algorithmic transparency demands that meet regulatory examination. Real-time processing abilities must synchronize intricate workflows across various data sources while upholding stringent consistency and reliability standards vital for mission-critical banking functions. The combination of these elements forms platforms capable of enduring regulatory scrutiny while providing reliable performance at a large scale.